Decreasing albumin within normal range is associated with increased likelihood of ischemic heart disease. (3rd October 2022) - Coster, D; Kodesh, A; Fardman, A; Tiosano, S; Moshkovits, Y; Bernstein, D; Kaplan, A; Shamir, R; Maor, E
Abstract: Background: Albumin (ALB) is a known biomarker of frailty, and cardiovascular disease and frailty are interdependent. Epidemiological evidence demonstrates that low serum albumin levels are linked to events of ischemic heart disease (IHD), venous thromboembolism, heart failure, atrial fibrillation, and stroke. Purpose: We aimed to investigate the association of variations in ALB levels that are within normal range with IHD events among apparently healthy adults. Methods: A case-control retrospective study of self-referred adults participating in an executive screening program between 2002 and 2017. All subjects were free of IHD and diabetes at baseline and had their ALB documented in each visit. Only subjects with at least two ALB measurements and whose ALB levels were within the normal range at all visits were included. Relationships between ALB trend and occurrence of IHD (acute coronary syndrome or percutaneous coronary intervention) within 2 years from the last visit were investigated. Results: The final study cohort included 16, 386 subjects. Median age was 53 (IQR 45–60), 11, 461 (70%) were men. Analysis included a total of 99, 127 visits. Median number of visits per subject was 5 (IQR 3–9, median inter-visit time 1.02 years) and median ALB level was 4.4 (IQR 4.2–4.6). IHD within 2 years was diagnosed in 545 (3%) subjects. Of those, only 36 were female and they tended to have lower variations in ALB throughout the years. Hence, we conducted an analysis of the 509 males only, and created an equal-size age-matched cohort of IHD-free subjects. Our analysis demonstrated a progressive and significant decrease in ALB levels among IHD cases, but not among controls (mean decrease of 0.021 g/DL vs. 0.004 g/DL per year, p<0.01; OR [CI] = 0.82 [0.72–0.93]; Figure 1). Similar results were found among subjects with at least 3 or 4 visits (0.015 g/DL vs. 0.006 g/DL per year, p=0.027, and 0.009 g/DL vs. 0.003 g/DL per year, p=0.045, respectively). Conclusions: Kinetics of ALB within the normal range can identify men at risk for IHD in preventive healthcare screening programs. Funding Acknowledgement: Type of funding sources: None.